2023
DOI: 10.1098/rsif.2022.0809
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanics of the finger pad in response to torsion

Abstract: Surface skin deformation of the finger pad during partial slippage at finger–object interfaces elicits firing of the tactile sensory afferents. A torque around the contact normal is often present during object manipulation, which can cause partial rotational slippage. Until now, studies of surface skin deformation have used stimuli sliding rectilinearly and tangentially to the skin. Here, we study surface skin dynamics under pure torsion of the right index finger of seven adult participants (four males). A cus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 49 publications
1
6
0
Order By: Relevance
“…However, we observed significant differences in the behavior of the skin across participants, with some participants presenting large skin deformations and others presenting very small deformations. Similar variability between participant finger pad skin behavior has been observed in passive studies (du Bois de Dunilac et al 2022, Wang and Hayward 2007). du Bois de Dunilac et al 2022 observed that the skin deformation rate varied significantly across participants, leading to significant differences in the timing of strains during the rotational load.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations

Open-source instrumented object to study dexterous object manipulation

Córdova Bulens,
du Bois de Dunilac,
Delhaye
et al. 2023
Preprint
Self Cite
“…However, we observed significant differences in the behavior of the skin across participants, with some participants presenting large skin deformations and others presenting very small deformations. Similar variability between participant finger pad skin behavior has been observed in passive studies (du Bois de Dunilac et al 2022, Wang and Hayward 2007). du Bois de Dunilac et al 2022 observed that the skin deformation rate varied significantly across participants, leading to significant differences in the timing of strains during the rotational load.…”
Section: Discussionsupporting
confidence: 78%
“…1E). The complete details of the strain computation can be found in Delhaye et al 2016 and du Bois de Dunilac et al 2022.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation

Open-source instrumented object to study dexterous object manipulation

Córdova Bulens,
du Bois de Dunilac,
Delhaye
et al. 2023
Preprint
Self Cite
“…For example, in situations when greater lateral forces cause a relatively large net, skin displacement occurs on a less slippery surface than with a more slippery surface. One alternative possibility to reduce ambiguity of contact forces and skin displacement in a real‐life situation requires combining the magnitude of skin displacement with information about the skin stretch pattern caused by the lateral movement (Ingvars et al., 2001, 2009; Seizova‐Cajic et al., 2014) or torsion in the finger pad (du Bois de Dunilac et al., 2023; Khamis et al., 2015; Loutit et al., 2023). As in virtual environments, tangential skin stretches within the contact area ranging between 0.25 and 0.75 mm lead to friction perception (Kamikawa & Okamura, 2018; Provancher & Sylvester, 2009; Santello et al., 2002; Suchoski et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…For example, when a relatively larger net skin displacement occurs on a less slippery surface, caused by an overall larger lateral movement than with a more slippery surface. One of alternative possibilities to reduce ambiguity due to variability of contact kinematics in real life situation is that the magnitude of skin displacement must be viewed in the context of the skin stretch pattern caused by lateral movement or torsion in the finger pad (Khamis et al, 2015; Dunilac et al, 2023; Loutit et al, 2023). As in virtual environments, tangential skin stretches within the contact area ranging between 0.25 - 0.75 mm leads to friction perception (Santello et al, 2002; Provancher and Sylvester, 2009; Kamikawa and Okamura, 2018; Suchoski et al, 2018).…”
Section: Discussionmentioning
confidence: 99%